Automated PTZ framing of track cyclists using timing loops - Slembrouck, M.; Decorte, R.; De Bock, J.; Verstockt, S. (Journal of Science and Cycling, 2023)
Track cycling coaches are mostly busy focussing on what their athletes are doing live. Therefore, they often lack the time to capture videos of the performances of their athletes during practice or competition from which the athletes can learn a lot. We propose a system that can automatically capture track cyclists using a PTZ camera and timing loops while limiting the amount of work for the coaches and technical staff.